Indicators to Monitor Deeper Regional Trade Integration in Africa - World Bank (Washington, DC, 2015)
Stronger regional integration has been a policy priority in Africa for several decades. Countries in Africa have committed to a process of deeper integration, but have made little progress in implementing commitments and removing barriers. This report looks at the monitoring of regional integration in Africa and argues that more effective monitoring processes for existing integration arrangements can help to raise the profile of the prevailing implementation deficits and provide policy makers and civil society with the necessary information to push for corrective action. Currently, most integration monitoring systems are scorecard-based compliance assessments. To obtain information on the impact of integration policies on ordinary traders, indicators of trade transaction costs are required. These can be indirect measures of trade volume changes or price differences, or direct estimates of the various trade cost components. The overall aim of this report is to explore indicators that capture the impact of regional policy reforms on trade transaction costs for ordinary traders, with a focus on indicators that can be linked to the implementation of specific policy measures. The report is organized as follows: section one gives introduction. Section two briefly discusses integration monitoring systems and related indicators in general. Section three presents an overview of regional trade indicators that are currently used by policy makers in Sub-Saharan Africa. Section four discusses the three main types of indicators, compliance with integration commitments, outcomes indirectly and at an aggregate level, and capturing specific trade cost components either directly or indirectly. Section five focuses on generating new indicators from new types of data sources; and section six discusses the way forward.